Designing and testing the high-purity germanium gamma-ray spectrometer for the Dragonfly mission to Titan - Hines, Nathan Robert (Kansas State University, 2022)
The Dragonfly Mission will send a high-purity germanium gamma-ray spectrometer one billion miles from Earth to investigate the composition of the icy world Titan, Saturn’s largest moon. The detector will be mounted on an autonomous rotorcraft and will travel over 100 miles across Titan's 94 K surface. A deuterium-tritium neutron generator will interrogate Titan's surface, producing gamma rays through neutron capture and inelastic scatter interactions. The gamma-ray spectrometer will measure these gamma-rays to determine the elemental composition of Titan's surface. The spectrometer was designed to operate in this unique environment, and was subjected to multiple tests to ensure design viability. The system was shown to be operable after being subjected to rocket-launch like vibration loads. A model was developed to simulate detector thermal performance and was shown to be accurate by comparison to experimental data. The model predicts that the detector will passively cool to an operating temperature of 100 K within seven days of the detector arriving on Titan’s surface, meeting mission requirements. The ability to anneal, or heat, the germanium crystal to repair radiation damage under Titan-like thermal conditions was demonstrated. Annealing the detector for a low input power requires that vacuum be maintained inside the cryostat. Vacuum performance was thoroughly characterized, and long-duration vacuum maintenance was demonstrated using a non-evaporable getter. Additionally, sensitivity to neutron-induced gamma rays was demonstrated under Titan-like conditions. A radiation damage study was performed to investigate 1) the effects of neutron damage on germanium energy resolution and 2) the anneal time required to repair neutron damage. A correlation between neutron fluence and spectrometer energy resolution is presented and an anneal recipe is provided.
Keywords: High-purity germanium detector; Radiation lattice damage; Gamma-ray spectroscopy; Vacuum; Dragonfly mission; Titan